A case report of successful elimination of recurrent ventricular tachycardia by repeated stereotactic radiotherapy: the importance of accurate target volume delineation - Peichl, Petr; Sramko, Marek; Cvek, Jakub; Kautzner, Josef (European heart journal. Case reports, 2021)
BACKGROUND: Stereotactic body radiotherapy (SBRT) has emerged recently as a novel therapeutic alternative for patients with ventricular tachycardias (VTs) resistant to convetional treatment. Nevertheless, many aspects related to SBRT are currently unknown. CASE SUMMARY: A 66-year-old man with ischaemic heart disease, a history of coronary artery bypass graft surgery and left ventricular dysfunction was referred for recurrent symptomatic episodes of slow VT (108 b.p.m.). The arrhythmia was resistant to antiarrhythmic drug therapy with amiodarone and repeated catheter ablation. The patient was scheduled to SBRT, however, the first session failed to suppress VT recurrences. After 20 months, the patient underwent re-do ablation procedure that revealed a newly developed scar with its core adjacent to the presumed critical part of the VT substrate. Catheter ablation again failed to eliminate VT and the second session of SBRT was scheduled. To improve targeting of the VT substrate for SBRT, we applied our recently developed original method for integration of data from the electroanatomical mapping system with computer tomography images. The second session of SBRT with precise targeting using the novel strategy led within 3 months to the successful elimination of VT. DISCUSSION: This case report describes a patient in whom the recurrent VT was abolished only by properly targeted SBRT. Above all, the case highlights the importance of precise identification and targeting for SBRT. Our case also documents in vivo, by electroanatomical voltage mapping, the development of SBRT-related myocardial lesion. This represents an important mechanistic proof of the concept of SBRT.
Keywords: Case report; Ventricular tachycardia; Catheter ablation; Stereotactic radiotherapy